2021
DOI: 10.3390/microorganisms9071450
|View full text |Cite
|
Sign up to set email alerts
|

Pre and Probiotics Involved in the Modulation of Oral Bacterial Species: New Therapeutic Leads in Mental Disorders?

Abstract: This systematic review aims to identify probiotics and prebiotics for modulating oral bacterial species associated with mental disorders. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guideline, we search the electronic MEDLINE database published till January 2021 to identify the studies on probiotics and/or prebiotics for preventing and treating major oral dysbiosis that provokes mental disorders. The outcome of the search produces 374 records. After excluding non-relevant studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Nutraceuticals are known for their health benefits: reduction of the risk of cancer and heart disease, but also the prevention or treatment of hypertension, hypercholesterolemia, overweight, osteoporosis, diabetes, arthritis, digestive disorders, and constipation, not to mention headaches [ 57 , 58 , 59 ]. It was shown that nutraceuticals may have therapeutic properties such as anti-inflammatory and antibacterial effects that may be beneficial for the treatment of periodontitis [ 60 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…Nutraceuticals are known for their health benefits: reduction of the risk of cancer and heart disease, but also the prevention or treatment of hypertension, hypercholesterolemia, overweight, osteoporosis, diabetes, arthritis, digestive disorders, and constipation, not to mention headaches [ 57 , 58 , 59 ]. It was shown that nutraceuticals may have therapeutic properties such as anti-inflammatory and antibacterial effects that may be beneficial for the treatment of periodontitis [ 60 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…Its use could help to reduce oral dysbiosis linked to PD [ 81 ] and its impacts on AD patients. Probiotic strains affecting the periodontogenic flora through various galenic forms, such as milk drinks, yoghurts, and mouthwash could facilitate oral hygiene measures in AD patients [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently there has been renewed interest in understanding microbial behavior in natural habitats. Many chronic diseases can have complex etiologies (sometimes not conforming to classic Koch postulates) and there is mounting evidence for microbial interventions in a plethora of pathologies in the human host ( Thomas et al, 2021 ), many of which are potentially either instigated or sustained by dysbiosis within the oral microbiome ( Le Bars et al, 2017 ; Tiwari et al, 2020 ; Maitre et al, 2021b ; Nguyen et al, 2021 ; Todorov et al, 2021 ; Gao et al, 2022 ; Rismayuddin et al, 2022 ; Sankarapandian et al, 2022 ). We all harbor personalized microbiomes based within our oral cavity biofilms, the balanced operations of which are a critical factor in our health status within the mouth -and beyond.…”
Section: Future Prospects For Oral Probioticsmentioning
confidence: 99%